2004
DOI: 10.1111/j.1439-0531.2004.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Thoroughbred Mares in Sweden

Abstract: During 1997-2001, a total of 430 Thoroughbred mares were mated by one of the two Thoroughbred stallions on a well-managed stud farm in the central part of Sweden. On arrival, a thorough gynaecological examination of all mares was performed. An early pregnancy examination was performed on days 14 and 15 after ovulation. The overall conception rates for the two stallions were 92.2 and 88.8%, and the corresponding live foal rates were 82.6 and 75.2%, respectively. The mean number of served oestrous cycles was 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
44
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 10 publications
19
44
7
Order By: Relevance
“…This was in contradiction with the supposed negative effect of lactation on fertility [6][7][8]. Instead of lower pregnancy losses [6] and other fertility results [49], maiden mares appeared as significantly lower reproducers (21% less than barren mares).…”
Section: Resultscontrasting
confidence: 47%
“…This was in contradiction with the supposed negative effect of lactation on fertility [6][7][8]. Instead of lower pregnancy losses [6] and other fertility results [49], maiden mares appeared as significantly lower reproducers (21% less than barren mares).…”
Section: Resultscontrasting
confidence: 47%
“…Bruck et al (1993) reported a foaling rate of 69% for Australian Thoroughbreds in the 1980s; higher results were achieved in Sweden (Hemberg et al 2004) and the United Kingdom (Morris and Allen 2002) over the past decades, but worse results can also be found in the literature Á 63% fertility in Brazilian horses (Taveira and da Mota 2007). Foaling rate was stable over the analyzed period with a slight increase since the 1960s (Fig.…”
Section: Foaling Ratementioning
confidence: 91%
“…In 1980's the results improved: the seasonal pregnancy rates ranged from 72 to 89% and the foaling rates from 66 to 77% (Ricketts and Young 1990, Brück 1993, Morris and Allen 2002. In 1990's a further improvement took place: a seasonal pregnancy rate of 92% and a foaling rate of 83% was achieved in 1997-2001 in Sweden (Hemberg et al 2004), and respectively, 95% and 83% in U.K. in 1998 (Morris and Allen 2002).…”
Section: Development Of Reproductive Efficiencymentioning
confidence: 74%
“…The age, when the mare fertility starts to decrease, varies from 10 to 15 years in different publications (Hutton and Meacham 1968, Laing and Leech 1975, Hearn et al 1993, Morris and Allen 2002, Hemberg et al 2004, Langlois and Blouin 2004 also the risk for the pregnancy loss increases at a similar age. The decreasing pregnancy rates and increasing pregnancy loss rates lead to low foaling rates.…”
Section: Effect Of Agementioning
confidence: 99%
See 1 more Smart Citation